Empowerment Communication of Madurese Women through Community-Based Ecotourism - Nikmah Suryandari; Farida Nurul Rahmawati; Qoniah Nur Wijayani; Nadya Poernamasari; Yuliana Rakhmawati; Netty Dyah Kurniasari (Jurnal Pemberdayaan Masyarakat, 2025)
This study examines how Madurese women utilize culturally ingrained communication methods to achieve empowerment through community-based ecotourism in Sumenep Regency, East Java. The research employed a qualitative ethnographic case study based on the Fiji Vanua Research Framework (FVRF), engaging 15 women entrepreneurs through participant observation, focus group discussions, and Talanoa-style interviews tailored to Madurese cultural conventions. The results indicate that informal social settings—such as pengajian (religious study groups), arisan (rotating savings groups), and cangkrukan (casual gatherings)—function as reliable platforms for discourse, identity negotiation, and communal learning. Instead of challenging patriarchal standards, women recontextualize traditional values such as bhuppa', bhabbu', guru, and rato to validate their economic and civic participation. These communication tactics promote social visibility, reciprocal support, and incremental changes in gender dynamics. The study underscores the significance of culturally rooted empowerment communication in traditional societies and enhances participatory development theory by highlighting localised, non-confrontational avenues for women's agency.